Scope economies between indiscriminate and selective urban solid waste collection - Limin Jiang (2018)
Recycling is one possible option within municipal solid waste (MSW) management to deal with the growing quantities of MSW produced. Only a few scholars have analysed the costs of this service and asked the question whether municipal solid waste management service utilities benefit from providing waste disposal and recycling services jointly. This dissertation tries to answer this question in the Portuguese context. In other words, it tries to find whether there are economies of scope in the Portuguese municipal solid waste management market between waste collection and disposal and recycling services. To answer the question, this study estimates a cost function of the municipal solid waste collection and disposal and recycling services in Portugal. Using a panel of 260 Portuguese retail municipal solid waste management service providers observed from 2001 to 2015, a multi-output translog cost function is estimated. The index value for scope economies is -0.27, meaning diseconomies of scope have been found.